Caregiver's attitudes, beliefs, and experiences for influenza vaccination in Australian children with medical comorbidities. Issue 16 (10th April 2019) - Norman, Daniel A.; Danchin, Margie; Van Buynder, Paul; Moore, Hannah C.; Blyth, Christopher C.; Seale, Holly
Highlights: Caregiver's vaccine safety and efficacy belief impacted reported vaccine uptake. 80% of caregivers approved children's future influenza vaccination at hospital. 30% of children were reportedly offered previous influenza vaccination at hospital. Caregivers' most reported vaccine information source was hospital physicians. Abstract: Background: Influenza vaccination is recommended and funded for Australian children with medical comorbidities that increase their risk of severe influenza. Despite this, influenza vaccine coverage remains low within this population. We examined caregivers' attitudes and practices for influenza vaccination in children with medical comorbidities. Methods: Cross-sectional surveys were conducted with caregivers of children (6 months to <18 years old) with medical comorbidities attending sub-speciality paediatric outpatient clinics at the Royal Children's Hospital (Melbourne), Princess Margaret Hospital (Perth), and Leading Steps private paediatric clinic (Gold Coast). Multivariate linear regression was used to identify surveys responses predictive of receipt of influenza vaccination in 2017. Results: From the 611 surveys collected, 556 were suitable for analysis. Caregiver reported 2017 influenza vaccine coverage was 52.2% in children with medical comorbidities. Caregivers who believed influenza vaccines to be ≥50% effective were more likely to vaccinate their children (adjusted Odds Ratio [aOR]:3.79 (2.41; 5.96). Those who expressed concerns about vaccine side effects were less likely to vaccinate their children (aOR: 0.49 [95% CI: 0.30; 0.80]). Influenza vaccine uptake was significantly more likely for children who had been previously recommended influenza vaccination by their hospital-based physician (aOR: 4.33 [95% CI: 2.58; 7.27]) and had previously received a hospital-based vaccination (aOR: 3.11 [95% CI 1.79; 5.40]). Hospital-based physicians were also caregivers' most commonly reported source of trusted vaccination information (63.5%). Whilst only 29.3% of caregivers reported their child had been recommended influenza vaccination during a previous admission, 80.1% of caregivers stated they were receptive to their child receiving potential future influenza vaccinations during hospitalisations. Conclusions: Reported influenza vaccination coverage in children with medical comorbidities remains inadequate. An important finding of this study is that influenza vaccination recommendation by children's hospital physicians and previous vaccine receipt in hospital was associated with vaccine uptake. Opportunities for vaccination, especially during hospitalisation, must be examined.